WORD ORDER IN ANGKOLA LANGUAGE: A STUDY OF SYNTACTIC TYPOLOGY - Jamaluddin Nasution; Mulyadi Mulyadi (Universitas Islam Sumatera Utara (UISU), 2022)
This study aims to discover what and how the typology of Angkola Language (AL) is in word order as well as to determine its grammatical alliance. The application of qualitative methods was carried out descriptively to this study, it means that the data analyzed and the results are in the form of a phenomenon description. The stages in this research are data collection, data analysis, and presentation of data analysis results/conclusions. The conclusion of this study is the word order, namely: (1) declarative sentences in AL are in the pattern of: a) Verb + Subject + Object for intransitive; b) Verb + Object + Subject for transitive; (2) The negation sentences have 2 patterns: a) Negation + Subject + Verb + Object; b) Subject + Negation + Verb + Object; (3) Interrogative sentences have 3 patterns: a) Subject + Verb + Object; b) Verb + Subject + Object; and c) Passive-Verb + Subject + Object; and (4) Imperative sentences have 2 patterns: a) Verb + Object (subject disappears); and b) Verb + Subject + Object (similar to a declarative sentence). In AL, the argument Agent (A) behaves the same as the argument Subject (S) and is different from the argument Patient (P); therefore, this language pattern is classified as an accusative type. It is expected that there will be a syntactic typology researches in AL which examine the syntactic typology comprehensively as an effort to preserve and maintain local/ethnic languages.